Specificity and mechanism of TonB-dependent ferric catecholate uptake by Fiu - Yang, Taihao; Zou, Ye; Ng, Ho Leung; Kumar, Ashish; Newton, Salete M.; Klebba, Phillip E. (Frontiers in Microbiology, 2024)
We studied the Escherichia coli outer membrane protein Fiu, a presumed transporter of monomeric ferric catecholates, by introducing Cys residues in its surface loops and modifying them with fluorescein maleimide (FM). Fiu-FM bound iron complexes of the tricatecholate siderophores enterobactin (FeEnt) and glucosylated enterobactin (FeGEnt), their dicatecholate degradation product Fe(DHBS)2 (FeEnt*), the monocatecholates dihydroxybenzoic acid (FeDHBA) and dihydroxybenzoyl serine (FeDHBS), and the siderophore antibiotics cefiderocol (FDC) and MB-1. Unlike high affinity ligand-gated porins (LGP), Fiu-FM had only micromolar affinity for iron complexes. Its apparent KD values for FeDHBS, FeDHBA, FeEnt*, FeEnt, FeGEnt, FeFDC and FeMB-1 were 0.1, 0.7, 0.7, 0.9, 0.3, 0.4, and 4 μM, respectively. The transport repertoires of E. coli Fiu, as well as those of Cir and FepA, were less broad. Despite binding FeDHBA, FeDHBS, FeEnt and FeGEnt, Fiu only transported FeEnt*. Cir transported FeEnt* and FeDHBS (weakly); FepA transported FeEnt, FeEnt* and FeDHBA; both Cir and FepA bound FeGEnt, albeit with lower affinity. Related transporters Acinetobacter baumannii (PiuA, PirA, BauA) had similarly moderate affinity and broad specificity for di- or monomeric ferric catecholates. The both microbiological and radioisotopic experiments showed Fiu's proclivity for, and transport of FeEnt*, rather than ferric monocatecholate compounds. Molecular docking and molecular dynamics simulations predicted 3 binding sites for FeEnt*in the external vestibule of Fiu, and a 4th site deeper in its interior. Alanine scanning mutagenesis in the outermost sites (1a, 1b and 2) decreased FeEnt* binding affinity as much as 20-fold, and reduced or eliminated FeEnt* uptake. Finally, the molecular dynamics simulations suggested a pathway of FeEnt* movement through Fiu, that may generally describe the process of metal transport by TonB-dependent receptors.